What Drives Educational Support for Children With Developmental Language Disorder or Autism Spectrum Disorder: Needs, or Diagnostic Category? - Dockrell, Julie E.; Ricketts, Jessie; Palikara, Olympia; Charman, Tony; Lindsay, Geoff A. (Frontiers in Education, 2019)
A central conceptual change in the Warnock report was the shift from categorization of children and young people by handicap to the identification of individuals’ special educational needs (SEN). However, the focus on categories has persisted. Data were collected from schools about the support provided to two groups of children with SEN in mainstream schools, those with Developmental Language Disorder (DLD) and those with Autism Spectrum Disorders (ASD), in schools and by external professionals (speech and language therapists (SLTs), educational psychologists and other support services). The type and level of support provided was examined and the ways in which this differed between children with a diagnosis of DLD or ASD explored. We considered whether the support provided varied according to within child or contextual factors. In addition, change in the provision made over time was explored. To our knowledge this is the first study to concurrently recruit pupils with DLD and ASD from the same mainstream settings to examine differences and similarities in their profiles and the ways in which these impact on service delivery. The results demonstrated provision for children with DLD and ASD continues to be driven by diagnostic categories, and that children with ASD are significantly more likely to receive support from schools and SLTs, independent of children’s language, literacy, cognitive scores and behaviour. Driving amount of provision by diagnostic category limits the possibility of providing effective provision to meet the children’s individual language and learning needs. This raises serious questions about the allocation of support resources and, by corollary, indicates the likelihood currently of an inequitable allocation of support to children and young people with DLD.